Cryptoeconomics: expert evaluation methodology of ICO start-ups in the processes of financial innovation management - A. V. Vlasov; M. M. Abrekov (Russian Journal of Economics and Law)
Objective: to develop a new methodological approach to the evaluation of innovative projects and technological startups which organize ICO.Methods: method of comparative analysis, method of measurement, inductive method of cognition, logical methods of cognition.Results: the paper discusses the events taking place in the market of alternative finances and demonstrates a new methodological approach to assessing the investment and innovation potential of startups implementing the ICO procedure.The methodology of evaluating the ICO startups is presented, which enables to make a choice and selection of target projects groups in a particular field of activity (for example, in fintech, insurtech). The stages of this assessment are considered. The developed method has been applied in practice for the evaluation (rating) of ICO projects in the insurance sector, and showed its efficiency. Its use allowed the authors to identify the fraudulent project and choose the “best” one using the rating results. Scientific novelty: a methodology was created which enables to conduct expert evaluation of ICO projects.Practical significance: the main provisions of the article can be used in the evaluation of start-up projects, in the work on ratings development. Also, the method of expert evaluation can be used in academic and pedagogical activities on the subject of alternative finances - ICO.